Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Berpikir Kritis Siswa SMP Materi Sistem Persamaan Linear Dua Variabel: The Effect of Problem-Based Learning Model on the Critical Thinking Ability of Junior High School Students Two-Variable Linear Equation System Material - Sriwijayati, Anissa; Rahma Febriyanti; M. Ulul Albab (Discovery, 2024)
This research was conducted on 8th class students of Junior High School 1 Sugio on the material of a system of two-variable linear equations by applying a problem-based learning model with the aim of knowing the effect of problem-based learning on students' critical thinking skills. This study is a quantitative research. The data obtained in this study were from tests taking 8A and 8B samples. The data analysis technique used are the normality test, homogeneity test and hypothesis test. In the Independent Sample T-Test hypothesis test decision making criteria it is said that if the Sig. (2-tailed) < 0.05 then it is accepted. In this study Sig. (2-tailed) less than 0.05 (0.017 < 0.05). So the hypothesis test is accepted. So it can be concluded that using a problem-based learning model can influence the improvement of students' critical thinking skills in the matter of a system of two-variable linear equations.